2006
DOI: 10.1192/bjp.188.3.255
|View full text |Cite
|
Sign up to set email alerts
|

Rechallenge with clozapine following leucopenia or neutropenia during previous therapy

Abstract: No clear risk factor for repeat blood dyscrasias was identified. Despite this, after risks and benefits have been considered, rechallenge may well be justified in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 19 publications
6
90
0
5
Order By: Relevance
“…Furthermore, in some patients the risks of withholding treatment may be greater than the risk of rechallenge, and although overall rechallenge patients are 22 times more likely to develop agranulocytosis than clozapine-naïve subjects, the risk may be justified on occasion (Silvestrini et al, 2000). Demographic, haematological and outcome data of 53 patients (UK and Ireland) who were rechallenged with clozapine following leucopenia or neutropenia during previous clozapine therapy, but in whom it was felt that it was likely that the dyscrasia was not clozapine-induced, have been presented (Dunk et al, 2006). Twenty (38%) patients experienced a further blood dyscrasia (post-2002 criteria-see Table 7).…”
Section: Clozapine and Neutropeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in some patients the risks of withholding treatment may be greater than the risk of rechallenge, and although overall rechallenge patients are 22 times more likely to develop agranulocytosis than clozapine-naïve subjects, the risk may be justified on occasion (Silvestrini et al, 2000). Demographic, haematological and outcome data of 53 patients (UK and Ireland) who were rechallenged with clozapine following leucopenia or neutropenia during previous clozapine therapy, but in whom it was felt that it was likely that the dyscrasia was not clozapine-induced, have been presented (Dunk et al, 2006). Twenty (38%) patients experienced a further blood dyscrasia (post-2002 criteria-see Table 7).…”
Section: Clozapine and Neutropeniamentioning
confidence: 99%
“…There is likely to be an immune component since the reaction occurs more quickly and is more severe on rechallenge in patients who have developed clozapineinduced neutropenia (Dunk et al, 2006).…”
Section: Clozapine and Neutropeniamentioning
confidence: 99%
“…Rechallenge of clozapine has been reported in the case of clozapineinduced leucopenia (Dunk et al 2006;Stanulovic et al 2013). However, there is no literature which discussed rechallenging clozapine in the case of allergic reaction.…”
Section: Discussionmentioning
confidence: 98%
“…However, one study has shown that of 53 patients rechallenged with clozapine following an initial blood dyscrasia, 38% developed a further leucopenia or neutropenia. 11 Clozapine has been shown to activate some of the same apoptic pathways as chemotherapy, 12 but it is not clear if concurrent use has an additional harmful effect. 13 In many of the available case reports where neutropenia did occur, granulocyte-colony stimulating factor (G-CSF) was used to help increase white cell counts.…”
Section: Discussionmentioning
confidence: 99%